2007
DOI: 10.1017/s1740925x08000070
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of oligodendrocytes on the conduction velocity of action potentials along axons in the alveus of the rat hippocampal CA1 region

Abstract: Like neurons and astrocytes, oligodendrocytes have a variety of neurotransmitter receptors and ion channels. However, except for facilitating the rapid conduction of action potentials by forming myelin and buffering extracellular K(+), little is known about the direct involvement of oligodendrocytes in neuronal activities. To investigate their physiological roles, we focused on oligodendrocytes in the alveus of the rat hippocampal CA1 region. These cells were found to respond to exogenously applied glutamate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 0 publications
1
85
0
Order By: Relevance
“…Conduction velocity along myelinated axons has been shown to depend also on neuron-glia interactions (123,190,526,570). Importantly, depolarization of a single oligodendrocyte was found to increase the action potential conduction velocity of the axons it myelinates by ϳ10% (570).…”
Section: Modulation Of Conduction Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…Conduction velocity along myelinated axons has been shown to depend also on neuron-glia interactions (123,190,526,570). Importantly, depolarization of a single oligodendrocyte was found to increase the action potential conduction velocity of the axons it myelinates by ϳ10% (570).…”
Section: Modulation Of Conduction Velocitymentioning
confidence: 99%
“…Importantly, depolarization of a single oligodendrocyte was found to increase the action potential conduction velocity of the axons it myelinates by ϳ10% (570). Although the precise mechanism has not been yet fully elucidated, it may result from ephaptic interaction between the myelin depolarization and the axon (280; see also sect.…”
Section: Modulation Of Conduction Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…Each oligodendrocyte envelops between one and 30 axonal segments (called internodes), depending on the axon diameter 18) . From a molecular biological standpoint, oligodendrocytes possess various neurotransmitter receptors and ion channels [53][54] . Electrophysiologically, oligodendrocytes facilitate the rapid conduction of action potentials by forming myelin and buffering extracellular K + .…”
Section: Thick Clusters Of Astrocytic Filaments In the Distal (Anterimentioning
confidence: 99%
“…The CV and localization of axonal membrane proteins are known to be altered under certain pathological conditions, including demyelinating diseases, but they have not been shown to vary under nondemyelinating conditions. Recently Yamazaki et al (2007) showed that activation of oligodendrocytes could alter the CV of the axons it myelinates. Thus, the relationship between myelin and axon may not be stationary, but may in fact be dynamic.…”
Section: Introductionmentioning
confidence: 99%